Student Perspectives on the Grammar Translation Method in English Language Learning - Suhria, Suhria; Ilmi, Nurul (Scolae: Journal of Pedagogy, 2023)
In this quantitative survey, the researchers aimed to investigate students' attitudes, perceptions, and experiences concerning the Grammar Translation Method (GTM) in English language instruction. The study involved fifteen students in class X of SMKN 1 Dampal Selatan. A questionnaire was used as an experimental tool to assess grammar learning. Data collection and analysis utilized a snowball technique. The questionnaire responses indicated that students generally had a positive attitude towards learning English and were familiar with GTM. They believed that learning grammar through translation waseasier, often used dictionaries, and appreciated teacher assistance with challenging words. However, they found grammar learning more challenging than expected and considered consistent learning necessary. Grouping words by category was seen as helpful, and mastering tenses was considered important for forming sentences. While students were open to structured sentence formation based on tenses, they expressed a preference for group work over individual activities.